2006
DOI: 10.2134/agronj2005.0156
|View full text |Cite
|
Sign up to set email alerts
|

Seeding Practices, Cultivar Maturity, and Irrigation Effects on Simulated Grain Sorghum Yield

Abstract: Grain sorghum [Sorghum bicolor (L.) Moench] is adapted for use in dryland and irrigated cropping systems on the southern High Plains. Irrigation in this region relies on the declining Ogallala aquifer, and applications are transitioning from full to deficit evapotranspiration replacement. Our objective was to identify optimum planting date, population, row spacing, and cultivar maturity combinations to maximize grain sorghum yield using the SORKAM model and long-term weather records at Bushland, TX, for a Pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 19 publications
2
32
0
4
Order By: Relevance
“…Além disso, a escolha do espaçamento entre linhas de semeadura e o número de plantas por área mais adequado são de extrema importância por determinarem melhor aproveitamento de fatores abióticos como água, luz e nutrientes para que a cultura possa expressar todo o seu potencial (Albuquerque et al, 2012). Para o sorgo forrageiro e o sorgo granífero, alguns autores reportaram a importância do arranjo de plantas na obtenção de maiores rendimentos (Baumhardt & Howell, 2006;Jones & Johnson, 1997 …”
unclassified
“…Além disso, a escolha do espaçamento entre linhas de semeadura e o número de plantas por área mais adequado são de extrema importância por determinarem melhor aproveitamento de fatores abióticos como água, luz e nutrientes para que a cultura possa expressar todo o seu potencial (Albuquerque et al, 2012). Para o sorgo forrageiro e o sorgo granífero, alguns autores reportaram a importância do arranjo de plantas na obtenção de maiores rendimentos (Baumhardt & Howell, 2006;Jones & Johnson, 1997 …”
unclassified
“…No-till and greater residue management can lead to considerably less evaporation which can increase profits (Klocke et al, 2009). Under simulation, grain sorghum on average produces a 7 percent greater yield when row spacing is half of that of traditional 0.76 m row spacing (Baumhardt and Howell, 2006). Simulated grain sorghum yields also showed that to maximize yield for the whole field, it is better to increase irrigation on parts of the field and have complementary dryland areas than to limit irrigate the entire field (Baumhardt et al, 2007).…”
Section: Limited Irrigationmentioning
confidence: 93%
“…Grain sorghum responds to better conditions and adequate rainfall by increasing tillers per plant thus increasing panicles per area (Baumhardt and Howell, 2006). When drought stress impacts the plant between panicle initiation and flowering time, number of seeds set could be greatly reduced, but if the stress occurred after flowering, then the seed weight could be potentially impacted (Baumhardt and Howell, 2006).…”
Section: Yield Componentsmentioning
confidence: 99%
See 2 more Smart Citations